'I have high self‐compassion': A face‐valid single‐item self‐compassion scale for resource‐limited research contexts. (5th February 2022) - Zhang, Jia Wei; Howell, Ryan T.; Chen, Serena; Goold, Aleah Ruth; Bilgin, Begüm; Chai, Wen Jia; Ramis, Tamilselvan
Abstract: The original 26‐item Self‐Compassion Scale (SCS; Neff, 2003) and 12‐item Short‐Form Self‐Compassion Scale (SF‐SCS; Raes et al., 2011) are scales commonly used in cross‐sectional and longitudinal research to assess the global self‐compassion construct and its six facets. We introduce the Single‐Item Self‐Compassion Scale (SISC; 'I have high self‐compassion') to measure the global self‐compassion construct in time‐, space‐ and resource‐limited contexts (e.g., daily diaries, experience sampling and nationally representative surveys). Additionally, the SISC will expand knowledge about self‐compassion by providing researchers whose primary interest is not self‐compassion with a convenient, face‐valid option to measure self‐compassion. Across 10 samples (four cross‐sectional, four longitudinal and two 7‐day daily diary; N  = 2, 477), we demonstrated that the SISC has acceptable psychometric properties. Specifically, the SISC was temporally consistent, correlated adequately with the SCS and SF‐SCS, exhibited nearly identical correlational patterns when compared with the SCS and SF‐SCS with a wide range of criterion measures (e.g., self‐esteem, personality, affective and social functioning, mental health and demographic variables) and saved 12 min over a 7‐day diary. Results replicated among students, community samples and across the United States, Turkey and Malaysia. Thus, we provide the field with an alternative measure of the global self‐compassion construct that complements the SCS and SF‐SCS.